Graphic Narratives as Opportunities for Professional Learning - Julianna E. Lopez Kershen (University of Oklahoma Libraries, 2022)
In the graphic narrative Queen of the Sea, protagonist Margaret tells the story of her youth on a secret island. Multimodal texts can be used as a platform for academic inquiry, enticing the reader to closely engage with the visual images, text, and the interplay between the two. Studying the sociocognitive complexity of a text invites the reader to utilize theory-of-mind thinking to identify the mental states communicated in the narrative, as well as narratological constructs such as temporality and narrative empathy. As an opportunity for professional learning, this study analyzed the sociocognitive complexity of Dylan Meconis's graphic narrative Queen of the Sea, using theory-of-mind thinking as an analytic frame for reading and exploring. Findings of this investigation highlight the complexity of graphic narratives and argue for their use as instructional texts in the English classroom.